The illustrated atlas of archaeology - Rollin, Sue; Sington, Adrian (Essex, Eng. Longman, 1982)
Text, illustrations, and maps provide an overview of the science of archaeology, including excavation methods, restoration techniques, and the evolution of civilizations the world over as documented by archaeologists.
Keywords: Archaeology; Civilization, Ancient; Man, Prehistoric